Pro Cloud Native Java EE apps : DevOps with MicroProfile, Jakarta EE 10 APIs, and Kubernetes - Saeed, Luqman; Abdallah, Ghazy (Apress, 2022)
This professional guide to Java-based cloud native apps DevOps dives deeper into building and deploying production ready cloud native apps using the increasingly popular open source Eclipse MicroProfile framework, Jakarta EE 10 APIs and the most popular Kubernetes container orchestration tool. After a quick overview of Jakarta EE and MicroProfile, Pro Cloud Native Java EE Apps starts you on your way by walking you through a cloud-native Jakarta EE-based application case study that will be forged piece-by-piece over the course of the book. Next, you'll interject dependencies and data persistence capabilities as microservices to go with the case study app that you are building. Next, you'll employ the REST API using Jakarta REST APIs and the MicroProfile RESTClient. You'll also explore ways to add resilience to your app, keep count with metrics, check on your app's health, secure your app, and test and complete your production-ready cloud-native app. Finally, you'll dive into migrating a monolith to become a production ready cloud-native app. After reading this book, you'll be able to build your own production ready cloud-native Java app using Jakarta EE and MicroProfile. What You Will Learn Build and deploy a production-ready cloud-native Java app using MicroProfile, Jakarta EE and Kubernetes Migrate a monolith app to become a cloud-native app Employ Jakarta EE APIs such as Persistence, CDI and more Leverage the MicroProfile framework Explore configurations, resilience, metrics, health, security, and more for your cloud-native apps Who This Book Is For Those software developers and programmers with at least some prior experience using Jakarta EE, MicroProfile. At least some prrior Java experience is expected.